The Role of Digital Technology in Sustaining Team Effectiveness in Hybrid Organizations - Willis Arestria Ayu Anggini; Citra Anisa Tika Putri; Enjelina S; Taruna Alfariz (CV. Proaksara Global Transeduka, 2025)
Hybrid work models that combine office and remote activities have become a strategic choice for many organizations in the face of modern work dynamics. This research aims to explore the role of digital technology in supporting team effectiveness in a hybrid work environment. The qualitative approach is used through in-depth interviews with employees from various sectors who have worked in a hybrid manner for at least the last six months. The results show that digital technologies, such as online communication and collaboration platforms, play an important role in maintaining smooth communication, strengthening coordination, and increasing team productivity. In addition, technology also contributes to team motivation and engagement, as long as its use is accompanied by adequate digital literacy and adaptive leadership. This study emphasizes the importance of the right technology implementation strategy in order to be able to answer the challenges and maximize the potential of hybrid work systems in a sustainable manner.